Konsep Dasar Belajar dan Hasil Belajar - Sutra Awaliyah Darfin; Mutahharatul Jannah; Nurfadillah Nurfadillah; Nurhuda Nurhuda; Annisa Sarif; Nurul Wahyuni (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
Learning is a process of behavioral change that involves interaction between individuals and their environment. Learning outcomes are changes resulting from the learning process, both in cognitive, affective, and psychomotor aspects. This article aims to explain the concept of learning, factors that influence the learning process, and how learning outcomes are measured and evaluated. With this understanding, it is hoped that it can provide guidance for educators to optimize the learning process. Learning is very important to produce output in an educational process. A good understanding of the basic concepts of learning is needed by education actors such as teachers, lecturers and stakeholders in an educational unit.